Integration of ear and hearing care services in low and middle-income health systems: a systematic review and qualitative synthesis - De Kock, Carmen (Department of Public Health and Family Medicine, 2025)
Hearing loss is a global public health burden and mostly affects those living in low and middle-income countries (LMICs). Hearing loss is expected to significantly increase without public health interventions. One approach to address ongoing challenges is the World Health Organisation's recommendation for the integration of ear and hearing care (EHC) services into healthcare packages. However, little is known about EHC integration approaches particularly in LMICs additionally, these approaches have not been investigated through a health systems lens. This qualitative review aimed to describe the various approaches to the EHC service integration in LMICs and to identify enabling and constraining factors. We conducted a qualitative synthesis to describe the factors influencing EHC service integration experiences. We reviewed 850 records and included 17 studies, with a focus on LMICs, using adaptations of the Valentijn integration and World Health Organization EHC frameworks. Our investigation showed that most integration approaches in LMICs were at micro or individual level. Enabling factors for integration of EHC services were training, mentorship, collaboration, technology, inclusion of EHC in healthcare packages and investment in EHC services. Barriers were challenges with training, facilities and equipment, policy implementation and resourcing of EHC services. We further described factors influencing healthcare seeking behaviour and the use of integrated EHC services such as access and ability to pay, referrals systems, and communication and awareness. This study describes the complex nature of EHC integration and ways to support integration. Key considerations are the level of integration, training to address workforce issues and factors influencing service utilisation as we work towards health system strengthening.